New species and records of the quill mites of the genus Peristerophila Kethley, 1970 (Acariformes: Syringophilidae) associated with pigeons and doves (Aves: Columbiformes) - Kaszewska, Katarzyna; Skoracki, Maciej; Kosicki, Jakub Z.; Hromada, Martin (Zootaxa, 2020)
The fauna of the quill mite genus Peristerophila Kethley, 1970 (Acariformes: Prostigmata: Syringophilidae) associated with pigeons and doves (Aves: Columbiformes) is reviewed. In our study, we examined 109 species of columbiform hosts of which 28 species belonging to nine genera were infested by Peristerophila mites. In the analyzed mite material, six species of this genus were found including two new species described herein: P. geopelis sp. nov. from Geopelia cuneata, G. placida, G. striata, as well as Ocyphaps lophotes and P. leucomela sp. nov. from Columba leucomela. Additionally, eighteen new host species and many new locality records for the previously described taxa are reported.